Hepatoblastoma in Children With Congenital Portosystemic Shunts. Issue 4 (April 2016) - Lautz, Timothy B.; Shah, Sonam A.; Superina, Riccardo A.
Abstract : ABSTRACT: Two children developed hepatoblastoma concurrent with congenital portosystemic shunts (PSSs) (Abernethy malformations). Both underwent operative ligation of their PSSs. One received concurrent tumor resection, whereas the other was deemed initially unresectable and underwent biopsy followed by neoadjuvant chemotherapy. Although benign hepatic masses, such as focal nodular hyperplasia and nodular regenerative hyperplasia, are common in patients with Abernethy malformations, malignant tumors have also been documented and should always be considered in the differential diagnosis of a patient with a congenital PSS and a hepatic mass.